3D flow reactors: flow, hydrodynamics, and performance - Sharma, Mrityunjay; Reddy, Venkateswara S.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2014)
A device comprised of a sequence of converging or diverging units aligned either in an axisymmetric or nonaxisymmetric manner can be used as a continuous flow reactor. Here we report the analysis of flow and hydrodynamics (pressure drop, residence time distribution, and mass transfer) for an axisymmetric geometry of a 3D flow reactor for single phase and two-phase flows. CFD simulations of the single phase flow have been used for identification of the precise geometrical configuration. The sequence of converging units as a flow reactor has been found to always be better than the sequence of diverging units. The residence time distribution analysis also favored the choice of converging flow as a better option. The performance of the device was verified by successfully carrying out a highly exothermic two-phase aromatic nitration of benzaldehyde (Delta H-r approximate to -172 kg/mol) with fuming nitric acid.

Exploring the steady operation of a continuous pilot plant for the di-nitration reaction - Sharma, Mrityunjay; Acharya, Roopashree B.; Kulkarni, Amol A (Chemical Engineering & Technology, 2019)
Continuous-flow synthesis of the selective herbicide pendimethalin was demonstrated in both a laboratory-scale and a pilot-scale reactor using only concentrated nitric acid as nitrating agent. The di-nitration reaction follows second-order kinetics where the reaction is first order with respect to both reactant and nitric acid. The pinched-tube reactor was chosen for pilot-scale reactor fabrication due to its excellent mixing and mass transfer characteristics compared to a straight-tube reactor. The estimated mass transfer coefficient showed similar nature in the laboratory-scale and the pilot-scale pinched-tube reactor, ensuring similar performance at the pilot scale. Di-nitration in continuous flow, inline quenching, extraction, and phase separation are some of the salient features of the developed pilot plant. The importance of the start-up time for achieving steady state in the flow system at the large scale is highlighted.

Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up